Pendampingan Remaja SMKN 5 Surabaya Terhadap Bahaya Penyalahgunaan NAPZA dan HIV/Aids - Eva Flourentina Kusumawardani; Rubi Rimonda; Meutia Paradhiba; Perry Boy Chandra Siahaan; Firman Firdauz Saputra; Mardi Fadillah; Onetusfifsi Putra (Idea Pengabdian Masyarakat, 2022)
Adolescence is a period of transition and experiencing rapid development ranging from physical, psychological and intellectual organs so that it requires good and supportive assistance to properly recognize these changes. Management of psicology which is emotions in adolescents who are not directed will cause adolescents to enter into risky behavior including drug abuse and risky sexual behavior. Increasing awareness of adolescents about the dangers of drug abuse, health problems caused by drug abuse and risky sexual behavior that causes sexually transmitted infections (STIs) including HIV and Aids through peer educators was urgently needed by adolescents. The target of the service was the youth of Civil Vocational High School (SMKN) 5 Surabaya and in its implementation it worked with the youth community who are members of the SCARFS (School and Communities Caring for HIV & AIDS) community 30 people. The methods used in this service activity were lectures / counseling, discussions, questions and answers  (QnA) and evaluations using pre and post test questionnaires. The results of the service activities carried out received good enthusiasm from the participants. The enthusiasm of the participants was during the case discussion session, participants asked an average of 4 questions to the facilitator and there was an increase in knowledge about drugs and HIV/Aids.